Effects of transmyocardial jet revascularization with chitosan hydrogel on channel patency and angiogenesis in canine infarcted hearts1. Issue 2 (4th September 2012) - Zhou, Dayan; Xiong, Lu; Wu, Qi; Guo, Rui; Zhou, Zhiyi; Zhu, Que; Jiang, Yonghong; Huang, Jing
Abstract: The purpose of this study was to investigate whether transmyocardial jet revascularization (TMJR) with chitosan scaffolds retains channel patency and enhances angiogenesis after acute myocardial infarction (AMI) in a canine model. A total of 32 canines were randomly divided into four groups: myocardial infarction (MI), normal saline (NS), chitosan hydrogel (CH), and chitosan plus growth factor (CH + GF) groups. TMJR was performed surgically using a needle‐free injector from the epicardium of canines in the NS, CH, and CH + GF groups; channels were filled with NS, CH, and CH + GF, respectively. After 6 weeks, the patency of the channels and angiogenesis around the channels were assessed by hematoxylin–eosin staining, immunohistochemistry, and Masson's trichrome staining. Results suggest that the channels in the CH and CH + GF groups may retain patency with luminal endothelization. Moreover, the vessel densities of the NS, CH, and CH + GF groups were significantly higher than that of the MI group, and that of the CH + GF group was the highest ( p < 0.05). This study suggests that TMJR with chitosan scaffolds may help retain transmyocardial channel patency and enhance angiogenesis after AMI in canines. © 2012 Wiley Periodicals, Inc. J Biomed Mater Res Part A, 2013.